2021
DOI: 10.1155/2021/3428260
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Timing of Stent Removal on the Incidence of UTI, Recurrence, Symptomatology, Resistance, and Hospitalization in Renal Transplant Recipients

Abstract: Purpose. To evaluate the impact of early (<3 weeks) versus late (>3 weeks) urinary stent removal on urinary tract infections (UTIs) post renal transplantation. Methods. A retrospective study was performed including all adult renal transplants who were transplanted between January 2017 and May 2020 with a minimum of 6-month follow-up at King Abdulaziz Medical City, Riyadh, Saudi Arabia. Results. A total of 279 kidney recipients included in the study were stratified into 114 in the early stent removal grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…Nonetheless, the number of recipients who had urgent early removal of their stent was too low to yield conclusive statements. Our group had previously suggested that studying “UTIs related to urinary stent” defined as UTIs while the ureteral stent is still in vivo and up to two weeks after its removal is a better indicator of the impact of the timing of stent removal than reviewing UTIs for a total duration of 3 or 6 months after transplantation [ 29 ]. Multiple other studies have examined the impact of stent removal at different intervals form renal transplantation including at 4 weeks [ 30 ], 3 weeks [ 31 ], 2 weeks [ 32 ], one week [ 33 ], or 5 days [ 34 ] after renal transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the number of recipients who had urgent early removal of their stent was too low to yield conclusive statements. Our group had previously suggested that studying “UTIs related to urinary stent” defined as UTIs while the ureteral stent is still in vivo and up to two weeks after its removal is a better indicator of the impact of the timing of stent removal than reviewing UTIs for a total duration of 3 or 6 months after transplantation [ 29 ]. Multiple other studies have examined the impact of stent removal at different intervals form renal transplantation including at 4 weeks [ 30 ], 3 weeks [ 31 ], 2 weeks [ 32 ], one week [ 33 ], or 5 days [ 34 ] after renal transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…In many studies, a fi nding of ≥ 10 5 CFU/ml of urine was defi nied as a positive urine fi nding (3,9,10). According to the guidelines published by the Infectious Diseases Society of America (IDSA) asymptomatic bacteriuria is defi ned as the presence of at least one type of bacterial growth in urine with a bacterial count ≥ 10 5 CFU/ml irrespective of whether pyuria is present or not and if there are no symptoms or signs attributable to UTI (11).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated a benefit in reducing stent-related UTI if the ureteric stent is removed between 7 and 14 days, compared with beyond 4–6 weeks after transplantation [ 61 , 62 ]. However, the incidence of total UTI at 6 months post-transplantation was not different according to whether stents are removed early or late in one study [ 63 ]. Currently, we are trying to decrease the time to stent removal in our center to minimize the risk of stent-related UTI without increasing the risk of urologic complications.…”
Section: Discussionmentioning
confidence: 99%